RAMADAN FASTING AMONG PEOPLE WITH TYPE 2 DIABETES IN MALAYSIA IN THE DAR 2020 GLOBAL SURVEY - Hussein, Zanariah; Taher, Sri Wahyu; Ismail, Mastura; Yahaya, Zaiton; Keong, See Chee; Voon, Tong Chin; Chin, Wong Hui; Bahari, Rashidah (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION The Diabetes and Ramadan (DAR) Global survey was conducted to determine the impact of Ramadan fasting among people with diabetes in different geographical regions in 2020. We describe the characteristics and care among participants with type 2 diabetes in Malaysia. METHODOLOGY In this observational study, participants attending community- and hospital-based diabetes clinics consented to answer a physician-administered questionnaire within 10 weeks following the completion of Ramadan. The survey characterised their intentions to fast and duration of fasting during and after Ramadan. Hypoglycaemia and hyperglycaemia events experienced were analysed along with diabetes-related medications and lifestyle adjustments. Specific analysis were performed comparing age categories below and above 65 years. RESULTS There were 748 survey participants with a mean age of 54.4 years. Of these, 23.2% were above 65 years, and 50% had diabetes more than 10 years. Mean HbA1c was 8.5%; 64% had HbA1c >7.5%. The most common treatments were metformin (83.6%), sulphonylureas (30.7%) and insulin (57.9%). Concern for COVID-19 affected the decision to fast in 3%. Of the 94.7% participants who intended to fast during Ramadan, 95.5% were able to fast for at least 15 days. Diabetes-related illness was the reason to break fasting in 16.3%. Hypoglycaemia and hyperglycaemia (>300mg/dL) occurred in 17.8% and 10.6% of participants, respectively, with 4.8% and 2.7% requiring hospital consult for the respective complications. A break in fasting was done by 68.5% of those with hypoglycaemia, compared to 14.9% with hyperglycaemia. CONCLUSION This survey highlights the high rates of Ramadan fasting among people with T2D in Malaysia during the COVID-19 pandemic. Glycaemic complications occurred frequently, indicating the need to enhance Ramadan-focused diabetes education and self- monitoring to reduce and prevent complications. Pre-Ramadan assessment is essential to identify those at increased risk who should be advised against fasting.